Insulin Treatment of Hypertriglyceridemia During Pregnancy - Cheng, De-cui; Su, Yao; Li, Feifei; Xu, Xianming (Frontiers in Pharmacology, 2022)
Objective: This study aims to investigate the efficiency of insulin on the reduction of gestational lipid profiles and try to propose a real-world approach to assist clinicians. Methods: A retrospective, single-centered cohort study of 35 cases was conducted from October 2018 to July 2021 in Shanghai General Hospital. SPSS version 25.0 was performed to analyze the whole data. For continuous variables, a paired-sample t test was carried out on each variable to make a comparison between before and after treatment. Results: The average pre-pregnancy TGs and TCs of these patients were about 3.96 ± 1.42 mmol/L and 4.78 ± 1.18 mmol/L, respectively. The maximum of TG before insulin treatment was up to 64.62 and TC 20.43 mmol/L, which decreased to 17.34 and 4.92 mmol/L after intervention of the insulin drip. TG was noticed to fall by 77% and 12.71% of TG, respectively. The difference of TG and TC between pre-treatment and post-treatment were statistically significant (p < 0.01), while this difference has not been found in the other laboratory tests reports. The outcomes of newborns and mothers with management of insulin were proven to be improved. Conclusion: The use of insulin in the management of gestational hypertriglyceridemia is safe and efficient, and insulin may become a mainstream in the near future to mitigate serum TG and TC levels in the pregnancy period besides regulating the blood glucose level.